Neutron fluence in a Howitzer drum and construction of a water moderated neutron irradiator - Diaz Ruiz, Anilu S., author; Sudowe, Ralf, advisor; Johnson, Thomas, committee member; Fisher, Gwen, committee member (Colorado State University. Libraries, 2024)
The Department of Environmental and Radiological Health Sciences at Colorado State University is utilizing a variety of irradiators to study the effects of ionizing on materials and tissue. Two of these are neutron irradiators based on 1 Ci and 5 Ci plutonium/beryllium (PuBe) sources, respectively. Neutron activation analysis is utilized to measure the neutron fluence at various positions in a Neutron Howitzer containing the 5 Ci source and a water tank containing the 1 Ci source. By determining the neutron flux in both systems, neutron irradiation at different intensities will become available for future research at Colorado State University. Additionally, both the drum and tank will be excellent teaching tools as they demonstrate neutron moderation, neutron shielding, material activation, and fluence measuring. Manufactured by the Nuclear-Chicago Corporation, the Model NH-3 Neutron Howitzer Drum is constructed in such a fashion that the PuBe neutron source can be moved in and out of irradiation position. In the irradiation position, two samples may be exposed to neutrons from the source by placing them in one of two horizontal ports in the drum. Both drum and ports are shielded with paraffin, which allows moderation of the neutron flux to thermal energies. In the experimental study, multiple metal foils were activated in the drum by irradiating them up to the point of measurable activity. Using a High Purity Germanium (HPGe) detector, the activity of the foils is quantified. The results of the measurements were used to calculate the neutron fluence using known neutron capture cross-sections. The calculated neutron fluence was then compared to the neutron fluence determined through a computational model of the drum using the Monte-Carlo N-Particle transport code (MCNP). Using the principles and methods practiced on the Howitzer drum, a water moderated neutron tank was constructed as a secondary neutron irradiator. The compared experimental and modeled neutron fluence spectrum in the drum were used to derive an effective model for total neutron fluence with respect to spacing from the inner end of the sample channel (x) of y = 69759e-0.17x and thermal neutron fluence of y = 12035e-0.176x.
Keywords: neutron fluence; Neutron Howitzer; plutonium-beryllium; neutron flux; MCNP; neutron moderation